Extended Thematic Progression - Pablo Ortega Gil (Miscelánea: A Journal of English and American Studies, 2001)
Traditional and contemporary accounts of speech acts (Searle 1969, 1979; Wierzbicka 1987) display a great deal of variation regarding the categorization of the acts of threatening, inviting, and offering as either directive or commissive. Given that these three illocutionary types include both directive and commissive features, some speech act theorists, like Bach and Harnish (1979) and Hancher (1979), has postulated the existence of a borderline category of directive-commissive acts, whose members are equally directive and commissive. My aim in this paper is twofold. First, I provide arguments supporting the claim that, in contrast to Bach and Harnish’s and Hancher’s predictions, the illocutionary force of threats, invitations and offers is not directive and commissive in equal proportions. Second, I argue that it is not necessary to posit the existence of a new ad hoc category of directive-commissive speech acts. In the light of cognitive linguistics and prototype theory, the three illocutionary types under consideration can be accommodated as just borderline cases which occupy different intermediate positions along the continuum between the superordinate categories of directive and commissive illocutions.